Penerapan Sistem Informasi Manajamen Pendidikan dalam Pengelolaan Data di Madrasah Aliyah Negeri 1 Sungai Penuh - Seprianto Seprianto (Journal on Education, 2022)
The aims of this study was to find out how to implemented an education management information system in managing students' achievement score at the State Islamic senior High School Number 1 Sungai Penuh.The design of this research was qualitative research. The informants of this research were: the head master, teachers and academic staff at the state Islmic senior High School Number 1 Sungai penuh. Based on the results and discussion of the research, it can be concluded that: the application of the Education Management Information System in Management of students' achievement score at state Islamic senior high school number 1 sungai penuh has been maximized because most of teachers has been understand the applications that are applied in managing students' achievement score. Besides, the socialization also held by schools has been done. But, there are still obstacles are faced in the process of managing students' achievement score at state Islamic senior High School Number 1 sungai penuh. The implementation process of the homeroom teacher plays an important role in collecting students' achivement data in the form of students personal information, attendance and organization or extracurriculars, by asking students to fill in the form given. Meanwhile, in collecting data student scores are took from the teachers, namely daily scores and final semester scores. After all student data has been collected, the homeroom teacher inputs or enters the data into the digital students' achivement application. And for the subject teachers to collect students' achievement in the form of scores, both daily scores, midterm scores and final semester scores in the class where they are teaches. After the required data and student score are collected, then the data is processed or accumulated in order to obtain quality data. When inputting student data and student score, teachers are required to use ARD (Digital Report Card Application), but there are still teachers who do not understand how to use the application, but most already understand how to use it.